The numerical analysis of the acoustic streaming effect of a cavity acoustic black hole - Huang, Meilian; Liang, Xiao; Su, Liang; He, Xingyun; Li, Danni; Chu, Jiaming; Wang, Shengsheng; Liang, Haofeng; Zhang, Yongyan (Frontiers in Materials, 2022)
In this study, we use numerical methods to study the acoustic streaming effect of the acoustic black hole (ABH). Firstly, we build an ABH model to study the acoustic streaming effect. By deriving the waves equations and solving the Navier–Stokes equations, we obtain the flow field, sound field, and temperature field under the acoustic excitation. Secondly, the simulation result reveals the mechanism of acoustic streaming effects on the sound transmission characteristics of cavity ABH. The numerical results show that the abrupt decrease in the sound pressure is caused by the great changes in the velocity gradient caused by the catastrophe of cross section. The energy of the sound waves can also be dissipated by the thermal viscous layer at low frequencies. Finally, based on the acoustic streaming effects of the acoustic medium in the ABH, we propose feasible methods to enhance the sound insulation. Increasing the cross section of the cavity in ABH can get a better sound insulation effect at high frequencies, and decreasing the cross section can improve Sound Transmission Loss (STL). Through optimization, STL can reach more than 25 dB at low frequencies.